E-wastes in the Philippines issues and measures. - Peralta, Genandrialine L.
The continuous dependence on electronic equipment at home and in the workplace has given rise to a new environmental challenge: electronic wastes. Electronic wastes or e-wastes refer to electronic products that no longer satisfy the needs of the initial purchaser. These can include a wide variety of goods such as computers, cellular phones, TVs, refrigerators, air conditioners, washing machines, video cameras, etc. These equipment contain hazardous materials such as lead, beryllium, mercury, cadmium, and chromium that pose both an occupational and environmental health threat. Although electronic equipment are considered safe during use, the potential for release of their toxic ingredients increase during storage or disposal. Because of the growing number of discarded electronics resulting from rapid product obsolescence, this type of waste is an emerging concern among developing countries. In the Philippines, a study estimates the current and future volume of E-wastes with focus on televisions, refrigerators, air conditioners, washing machines and radios. Data from the National Statistics Office (NSO) serve as input to a simple end-of-life model for each electronic type. Then, mathematical equations are derived incorporating other factors such as volume of electronics in use, current end-of-life management practices, serviceable years of the product and disposal behavior of consumers. The accurate estimation of E-waste generation would be useful in policy making as well as in designing an effective management scheme to avoid potential threat as health impact or environmental pollutant. Preliminary estimates show that at the end of 2004, approximately 3 million units will become obsolete and by 2010 this amount will increase 1.5 times.
Keywords: Electronic wastes; E-wastes estimation; Philippines